Sense of Belonging Masyarakat Rasau Jaya dalam Meningkatkan Civic Engagement serta Virtues - pratiwi, Endang Maya; Bistari, Bistari; Utami, Tri; Amrazi; Atmaja, Thomy Sastra; Zakso, Amrazi (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This study aims to describe the sense of community belonging that can increase community involvement and develop values ​​of virtue in the community. The research method used is a qualitative approach through observation, in-depth interviews, and documentation. The results of the study indicate that the forms of community involvement include the community being able to contribute, organize, carry out actions or actions, motivate each other, and be responsible for involvement in activities, as well as the values ​​of community virtue that develop as supporters in the implementation of actions. The sense of belonging is based on four indicators in the form of a strong sense of belonging, pleasure, commitment, and having a moral level. There are supporting factors for community involvement, in the form of opportunities, awareness, ability, community interests, and encouragement from the village government, and the inhibiting factors that arise are the lack of opportunities and community awareness. More efforts are needed to motivate and provide understanding to awaken the sense of community belonging.